Watching Every Step of the Way: Junín Virus Attenuation Markers in the Vaccine Lineage - Ines Stephan, Betina; Enrique Lozano, Mario; Elizabeth Goni, Sandra (Current Genomics, 2013)
The Arenaviridae family includes several hemorrhagic fever viruses which are important emerging pathogens. Junín virus, a member of this family, is the etiological agent of Argentine Hemorrhagic Fever (AHF). A collaboration between the Governments of Argentina and the USA rendered the attenuated Junín virus vaccine strain Candid#1. Arenaviruses are enveloped viruses with genomes consisting of two single-stranded RNA species (L and S), each carrying two coding regions separated by a stably structured, non-coding intergenic region. Molecular characterization of the vaccine strain and of its more virulent ancestors, XJ13 (prototype) and XJ#44, allows a systematic approach for the discovery of key elements in virulence attenuation. We show comparisons of sequence information for the S RNA of the strains XJ13, XJ#44 and Candid#1 of Junín virus, along with other strains from the vaccine lineage and a set of Junín virus field strains collected at the AHF endemic area. Comparisons of nucleotide and amino acid sequences revealed different point mutations which might be linked to the attenuated phenotype. The majority of changes are consistent with a progressive attenuation of virulence between XJ13, XJ#44 and Candid#1. We propose that changes found in genomic regions with low natural variation frequencies are more likely to be associated with the virulence attenuation process. We partially sequenced field strains to analyze the genomic variability naturally occurring for Junín virus. This information, together with the sequence analysis of strains with intermediate virulence, will serve as a starting point to study the molecular bases for viral attenuation.
Keywords: Point mutations